1993
DOI: 10.1111/j.1460-9568.1993.tb00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thiol Reagents on Phosphoinositide Hydrolysis in Rat Brain Synaptoneurosomes

Abstract: Some divalent ions, such as Cd2+ and Zn2+, are able to stimulate phosphoinositide (PI) breakdown and to inhibit receptor-mediated PI metabolism. These ions are also known to react with the free -SH groups of proteins. This prompted us to investigate the effects of more potent sulphydryl reagents, Hg2+ and p-chloromercuric benzosulphonic acid (PCMBS), on the inositol phosphate (IP) accumulation triggered by the neuroactive substances: glutamate, carbachol and K+, using synaptoneurosomes from 8-day-old rat foreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Mercury is known to inhibit enzyme activity by binding to sulfhydryl groups in cysteine or methionine residues often present at active sites. 25 Experiments with β-glucuronidase indicated that enzyme activity was unaffected in the presence of 100-fold higher molar concentration of mercury chloride than used for sample preservation (data not shown), consistent with the fact that the active site of this enzyme contains a glutamate residue, not a sulfhydryl group. 26 In the case of the effluent, there are indications that extracellular β-glucuronidase is produced by bacteria in wastewater during activated sludge treatment.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Mercury is known to inhibit enzyme activity by binding to sulfhydryl groups in cysteine or methionine residues often present at active sites. 25 Experiments with β-glucuronidase indicated that enzyme activity was unaffected in the presence of 100-fold higher molar concentration of mercury chloride than used for sample preservation (data not shown), consistent with the fact that the active site of this enzyme contains a glutamate residue, not a sulfhydryl group. 26 In the case of the effluent, there are indications that extracellular β-glucuronidase is produced by bacteria in wastewater during activated sludge treatment.…”
Section: Resultsmentioning
confidence: 57%
“…The inability of mercury to preserve glucuronide conjugates is consistent with the structure of glucuronidase enzymes that are likely responsible for the observed transformations. Mercury is known to inhibit enzyme activity by binding to sulfhydryl groups in cysteine or methionine residues often present at active sites …”
Section: Resultsmentioning
confidence: 99%
“…p-Chloromercuribenzoic acid (PCMB), an anionic probe of moderate size, caused the oocytes to swell and burst at a concentration of 0.2 mM (data not shown). This was attributed to the entry of PCMB into the oocytes by non-ionic diffusion and the subsequent inhibition of energy metabolism, since several steps in glycolysis and oxidative phosphorylation are known to be sensitive to sulphydryl reagents [25][26][27]. By contrast, p-chloromercuribenzosulfonate (PCMBS), a bulky anion believed to be membrane impermeant [14,28], did not cause the oocytes to burst and had little or no effect on wild-type CFTR-mediated Cl -currents, even at concentrations as high as 1.3 mM.…”
Section: +mentioning
confidence: 99%
“…[Ca2+]i measurements were performed by loading synaptoneurosomes with fura2 (Grynkiewicz ef al., 1985), by incubation with 5 pM of fura2-AM and 0.02% p h o n i c during 30 min at 37°C as previously described (Vignes et al, 1993). The preparation was alternately excited at 340 and 380 nm using an optical chopper (300 Hz).…”
Section: [Cand+li Measurementsmentioning
confidence: 99%